Hematology, Biochemistry Reference Intervals, and Morphological Description of Peripheral Blood Cells for a Captive Population of Crocodylus intermedius in Colombia - Barajas-Valero, Steven; Rodríguez-Almonacid, Cristian; Rojas-Sereno, Zulma; Moreno-Torres, Carlos; Matta, Nubia E. (Frontiers in Veterinary Science, 2021)
The Orinoco crocodile (Crocodylus intermedius, Graves, 1918) is the most threatened crocodilian of South America. There is only scarce information available about the physiology of this neotropical crocodile. This study aimed to propose baseline hematological and biochemistry reference data and intervals and a morphological description of the peripheral blood cells of captive C. intermedius. Blood was collected from 318 clinically healthy individuals maintained in captivity at Villavicencio, Colombia. Eight of these individuals were sampled and resampled, and these data were compared. Reference intervals were proposed for hematological values [packed cell volume (PCV), red blood cell count, white blood cell count, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, hemoglobin, and white blood cell count differential counts] and biochemistries [total solids, alanine aminotransferase (ALT), aspartate aminotransferase, alkaline phosphatase, lactate dehydrogenase, creatine kinase, glucose, albumin, cholesterol, uric acid, creatinine, and lactate] including adults and juveniles, males and females' crocodiles. Blood cell morphology for the species is described. Significant differences between sex and age were observed. The intraindividual analysis concluded differences for total solids (P ≤ 0.01) and red blood cell counts (P ≤ 0.01). Some biochemical analytes showed a moderate correlation between them, such as ALT–alkaline phosphatase and ALT–uric acid. We present here novel and baseline data with special importance for the clinical diagnosis, improving the national reintroduction programs from either in situ and ex situ populations.